Pleistocene basaltic volcanism in the southeastern Ailao Shan - Red River Shear zone: Implications for the injection of metasomatized asthenospheric mantle under the region - Nguyen, Hoang; Shinjo, Ryuichi; Le Duc, Luong; Tran Thi, Huong; Tran Viet, Anh; Phan Dong, Pha; Pham Thanh, Dang; Cu Sy, Thang; Nguyen Thi, Thu; Le Thi Phuong, Dung (Vietnam Journal of Earth Sciences, 2024)
The Lung Po basalt, dating to 0.93, 0.81, and 0.47 Ma, occupies approximately 1 km² and is situated 12 km west of the Ailao Shan Red River Shear Zone (ASRRSZ) and about 65 km south of the 12-0 Ma Maguan intraplate volcanic area in southwest Yunnan (SW China), within the ASRRSZ. This olivine-bearing phyric alkaline basalt is characterized by high TiO₂ (around 2.3 wt.%), MgO (8-10 wt.%), and K₂O (approximately 2.8-3 wt.%) with Na₂O/K₂O ratios ranging from 1 to 1.2. These features partially overlap with the Maguan mantle xenolith-bearing alkaline basalt but are distinct from the Pleistocene alkaline basalt of Vietnam’s Western Highlands. The Lung Po basalts exhibit a typical oceanic island basalt (OIB) trace element distribution pattern and a ’crossing’ rare earth element (REE) pattern, indicating magma generation possibly by melting of garnet peridotite. They have high ⁸⁷Sr/⁸⁶Sr isotopic ratios (around 0.706) and low ¹⁴³Nd/¹⁴⁴Nd ratios (approximately 0.5126), along with moderate ²⁰⁶Pb/²⁰⁴Pb and ¹⁷⁶Hf/¹⁷⁷Hf isotopic ratios (respectively <18.3-18.4 and 0.28295-0.2830). These isotopic characteristics, coupled with OIB trace element features, challenge the involvement of crustal material. The Lung Po Pleistocene basalt and the 12-0 Ma Maguan alkaline basalt differ significantly from the 42-24 Ma post-collision high-K magmas in the ASRRSZ, which are associated with crustal tectonic processes. Instead, the Lung Po (and Maguan) basalt likely originated from a newly emplaced, metasomatically altered fertile asthenosphere following localized lithosphere extension and delamination after the India-Eurasian collision events.